Construction de l’État, formation de la nation et violence légitime en Argentine et aux États-Unis (années 1860) : une expérience américaine ? - Félix Landry (Nuevo mundo - Mundos Nuevos, 2013)
This presentation offers some thoughts about American experiences of state violence in the XIXth century, that is during the pan-American nation-state building process. It aims to explain how Domingo Faustino Sarmiento, president of the Argentine Republic from 1868 to 1874, justified the use of violence in the repression of a revolt (Ángel ‘Chacho’ Peñaloza’s rebellion) during an anterior phase of his career. To do so, he mobilized what he believed, or pretended to believe, was the current state of war and repression law forged in the United States in the Civil War context. The justification of violence by the idea of a ‘colonial’ struggle against ‘barbarism’ is also discussed. From this example, it is attempted to ponder the nature of real and imaginary international ‘transfers’ of power practices and discourse about these practices.